Gianotti-Crosti syndrome as the only manifestation of primary Epstein-Barr virus infection: a case report - Gümüş, Pınar; Tekşam, Özlem; Akıncı, Hande; Boztepe, Gonca; Kara, Ateş (The Turkish Journal of Pediatrics, 2008)
Gianotti-Crosti syndrome (GCS) presents as a symmetric erythematous papular and papulovesicular eruption of the face, extremities, and buttocks, and usually occurs in young children. GCS has been classically associated with hepatitis B virus, as well as rarely with Epstein-Barr virus (EBV) and cytomegalovirus. We report a case of GCS related with EBV infection without any systemic symptoms in a two-year-old male patient who presented with symmetric red papular eruptions on the cheeks, buttocks and both upper and lower extremities.